2014
DOI: 10.1017/s0016756814000119
|View full text |Cite
|
Sign up to set email alerts
|

Geochronology of the Cambrian: a precise Middle Cambrian U–Pb zircon date from the German margin of West Gondwana

Abstract: A volcanic tuff 1.0 m above the base of the Triebenreuth Formation in the Franconian Forest provides the first precise and biostratigraphically bracketed date within the traditional Middle Cambrian. The first illustration of fossils from the Triebenreuth Formation in this report and their discussion allow a more highly refined correlation within the Middle Cambrian. A weighted mean 206Pb–238U date of 503.14±0.13/0.25/0.59 Ma on zircons from this subaerial pyroclastic tuff was determined by U–Pb chemical abrasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…23). This problem raises the question whether our results might change with further revisions of the timescale.…”
Section: Significancementioning
confidence: 99%
“…23). This problem raises the question whether our results might change with further revisions of the timescale.…”
Section: Significancementioning
confidence: 99%
“…As discussed by Landing et al (2014), Pigage et al's (2012) Lower Ordovician date is surprising for its great age-its reported 491 ± 0.13 Ma date is even older than a recalibrated U-Pb zircon date of 488.71 ± 1.17 Ma from Cambrian Stage 10 (discussed above). The consequences of assigning such seemingly "old" dates to the Cambrian, which are contrary to recently revised dates on the Ogof ddu and Bryn-llyn-fawr ashes (discussed above) and lead to their estimate of a very "old" Cambrian-Ordovician boundary age, were not by discussed in detail by Pigage et al (2012).…”
Section: Early Ordovician Datesmentioning
confidence: 94%
“…An illustration that seemingly precise dates on the ICS Chart are estimates that may obscure arguably "better" alternative estimates can be taken from the late Cambrian. As discussed by Landing et al (2014), the base of the traditional Upper Cambrian, or the part of the Guzhangian Stage immediately under the Furongian Series (Fig. 1) has long been estimated as 500 Ma, with 500.5 Ma appearing on the recent Charts .…”
Section: Precise Vs Estimated Datesmentioning
confidence: 98%
See 2 more Smart Citations